Genome-wide identification, classification and expression analysis of MYB gene family in coconut (Cocos nucifera L.) - Li, Jing; Guo, Shukuan; Min Htwe, Yin; Sun, Xiwei; Zhou, Lixia; Wang, Fangyuan; Zeng, Chunru; Chen, Shuangyan; Iqbal, Amjad; Yang, Yaodong (Frontiers in Plant Science, 2024)
MYB transcription factors regulate the growth, development, and secondary metabolism of plant species. To investigate the origin of color variations in coconut pericarp, we identified and analyzed the MYB gene family present in coconut. According to the sequence of MYB genes in Arabidopsis thaliana, homologous MYB gene sequences were found in the whole genome database of coconut, the conserved sequence motifs within MYB proteins were analyzed by Motif Elicitation (MEME) tool, and the sequences without conservative structure were eliminated. Additionally, we employed RNA-seq technology to generate gene expression signatures of the R2R3-MYB genes across distinctive coconut parts exhibiting diverse colors. To validate these profiles, we conducted quantitative PCR (qPCR). Through comprehensive genome-wide screening, we successfully identified a collection of 179 MYB genes in coconut. Subsequent phylogenetic analysis categorized these 179 coconut MYB genes into 4-subfamilies: 124 R2R3-MYB, 4 3R-MYB types, 4 4R-MYB type, and 47 unknown types. Furthermore, these genes were further divided into 34 subgroups, with 28 of these subgroups successfully classified into known subfamilies found in Arabidopsis thaliana. By mapping the CnMYB genes onto the 16 chromosomes of the coconut genome, we unveiled a collinearity association between them. Moreover, a preservation of gene structure and motif distribution was observed across the CnMYB genes. Our research encompassed a thorough investigation of the R2R3-MYB genes present in the coconut genome, including the chromosomal localization, gene assembly, conserved regions, phylogenetic associations, and promoter cis-acting elements of the studied genes. Our findings revealed a collection of 12 R2R3-MYB candidate genes, namely CnMYB8, CnMYB15, CnMYB27, CnMYB28, CnMYB61, CnMYB63, CnMYB68, CnMYB94, CnMYB101, CnMYB150, CnMYB153, and CnMYB164. These genes showed differential expressions in diverse tissues and developmental stages of four coconut species, such as CnMYB68, CnMYB101, and CnMYB28 exhibited high expression in majority of tissues and coconut species, while CnMYB94 and CnMYB164 showed lower expression. These findings shed light on the crucial functional divergence of CnMYB genes across various coconut tissues, suggesting these genes as promising candidate genes for facilitating color development in this important crop.